2018
DOI: 10.1515/raon-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary deep inspiration breath-hold reduces the heart dose without compromising the target volume coverage during radiotherapy for left-sided breast cancer

Abstract: BackgroundDuring radiotherapy of left-sided breast cancer, parts of the heart are irradiated, which may lead to late toxicity. We report on the experience of single institution with cardiac-sparing radiotherapy using voluntary deep inspiration breath hold (V-DIBH) and compare its dosimetric outcome with free breathing (FB) technique.Patients and methodsLeft-sided breast cancer patients, treated at our department with postoperative radiotherapy of breast/chest wall +/– regional lymph nodes between May 2015 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 42 publications
(78 reference statements)
0
11
1
Order By: Relevance
“…The DIBH plans demonstrated significantly larger total lung volume in their study. Differences in the lung dose between FB and DIBH plans were also not significant in the study by Al-Hammadi et al 20 Our study showed there was no significant difference in the Dmean and D50 of lungs between FB and BH plans.…”
Section: Comparison Of Lung Dosecontrasting
confidence: 47%
“…The DIBH plans demonstrated significantly larger total lung volume in their study. Differences in the lung dose between FB and DIBH plans were also not significant in the study by Al-Hammadi et al 20 Our study showed there was no significant difference in the Dmean and D50 of lungs between FB and BH plans.…”
Section: Comparison Of Lung Dosecontrasting
confidence: 47%
“…Radiation oncologists implement several methods to decrease IR dose to the heart for minimizing the risk of RACVD (76), such as prone positioning (77), heart block with electronic compensation (57), heart-sparing three-dimensional printing technique (78), continuous positive airway pressure (CPAP) (79), real-time position management (RPM) inspiration gating (80,81), proton-beam irradiation (82)(83)(84)(85), and deep-inspiration breath-hold technique (DIBH) (86)(87)(88)(89)(90). However, even with the highly recommended visual-guided DIBH technique, residual variations of the heart position are still noticeable (91).…”
Section: Clinical Challenges Of Decreasing the Risk Of Racvd In Modermentioning
confidence: 99%
“…If radiotherapy is delivered in a breath hold, which allows the heart to move down and posterior to the treatment volume, the sparing effect to the heart is even greater. 32 In a study comparing free breathing (FB) with voluntary deep inspiration breath hold (V-DIBH) resulted in a significant reduction of mean cardiac dose from 6.1 +/- 2.5 to 3.2 +/- 1.4 Gy (p < 0.001), maximum cardiac dose from 51.1 +/- 1.4 to 48.5 +/- 6.8 Gy (p = 0.005) and cardiac V25Gy from 8.5 +/- 4.2 to 3.2 +/- 2.5% (p < 0.001). There is no specific data for the dose to the pericard.…”
Section: Effect Of Radiation Dose and Techniques Of Treatment Planninmentioning
confidence: 99%